2014
DOI: 10.1093/cvr/cvu195
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging reveals that loss of the C-terminus of connexin43 limits microtubule plus-end capture and NaV1.5 localization at the intercalated disc

Abstract: NaV1.5 and EB1 localization at the cell end is Cx43-dependent. Cx43 is part of a molecular complex that determines capture of the microtubule plus-end at the ID, facilitating cargo delivery. These observations link excitability and electrical coupling through a common molecular mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 41 publications
3
107
0
Order By: Relevance
“…Na V 1.5 is trafficked to and delivered into the cell membrane by the microtubule network. Specific sites of delivery are determined by macromolecular complexes composed of anchoring and microtubule capture proteins 19, 24. In TAC hearts, increased protein expression levels of the microtubule protein α‐tubulin and plus‐end microtubule capture protein EB1 were observed, indicating a denser microtubule network and a potential increase in microtubule capture sites at the cell membrane (Figure 8A and 8B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Na V 1.5 is trafficked to and delivered into the cell membrane by the microtubule network. Specific sites of delivery are determined by macromolecular complexes composed of anchoring and microtubule capture proteins 19, 24. In TAC hearts, increased protein expression levels of the microtubule protein α‐tubulin and plus‐end microtubule capture protein EB1 were observed, indicating a denser microtubule network and a potential increase in microtubule capture sites at the cell membrane (Figure 8A and 8B).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used superresolution localization microscopy (STORM) to resolve the molecular organization of Na V 1.5 in fixed cardiomyocytes isolated from Sham and TAC ventricles, with a lateral resolution of 20 nm 19, 24. No differences in Scn5a mRNA levels or total Na V 1.5 protein levels were observed between Sham and TAC ventricular tissue (Figure 9A through 9C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Recent studies have shown that these intercellular formations may also play a role in signal transduction, apoptosis, and adipogenesis. 8 Early histology and electron microscopy studies revealed that the fibrofatty replacement of the right ventricular myocardium is accompanied by inflammation and apoptosis. 9 Desmosomal mutations may lead to altered cellular distribution of desmosomes, as well as increased apoptosis.…”
mentioning
confidence: 99%